Sistem Informasi Customer Relationship Management Pada Hotel Grand Malaka Ethical Palembang Berbasis Web - Mutia Rizky Pratiwi; Fithri Selva Jumeilah; Fathiyah Noprian (APTIKOM SUMSEL, 2020)
Grand Malaka Ethical is a sharia hotel located in Palembang City with a three-star classification, located on Jalan Malaka II No.5. With the rapid development of technology today, many hotel booking applications that provide star-rated hotels with cheap and good prices make Hotel Grand Malaka must compete with other hotels in order not to be left behind. Grand Malaka Ethical Hotel still uses minimal applications and recently hotel visitors continue to decline. This study aims to create a web-based Customer Relationship Management Information System using the Prototype system development method. This research has produced a Web-based Customer Relationship Management Information System at the Grand Malaka Ethical Palembang Hotel that has been tested and will be implemented by the hotel in 2021.